Mass flow rate induced by combines roof solar collector and vertical stack in a hot humid climate - Mohammad Yusoff, Wardah Fatimah; Sapian, Abdul Razak; Salleh, Elias; Adam, Nor Mariah; Hamzah, Zabidi (College Publishing, 2014)
This paper presents the investigation of solar induced ventilation that utilizes roof solar collector and vertical stack. Three prototypes, namely A, B and C, were developed based on preliminary experimental work. They were then used in simulation study with the objective of determining the prototype that was able to induce the highest mass flow rate. The validation of simulation modelling against experiment indicated a good agreement between these two results. The findings showed that prototype A induced the highest mass flow rate. However, prototype C, which had obstructions at the stack outlets, was more appropriate for application in Malaysia due to various prevailing wind directions. In addition, the findings also indicated that besides solar radiation, the mass flow rate induced by the prototypes was also influenced by the local wind direction, the inlet and outlet positions as well as the outlet design. In summary, the findings highlighted the potential application of the proposed solar induced ventilation in a hot and humid climate.